Laser radar: historical prospective-from the East to the West - Molebny, Vasyl; McManamon, Paul; Steinvall, Ove; Kobayashi, Takao; Chen, Weibiao (Optical engineering, 2017)
This article discusses the history of laser radar development in America, Europe, and Asia. Direct detection laser radar is discussed for range finding, designation, and topographic mapping of Earth and of extraterrestrial objects. Coherent laser radar is discussed for environmental applications, such as wind sensing and for synthetic aperture laser radar development. Gated imaging is discussed through scattering layers for military, medical, and security applications. Laser microradars have found applications in intravascular studies and in ophthalmology for vision correction. Ghost laser radar has emerged as a new technology in theoretical and simulation applications. Laser radar is now emerging as an important technology for applications such as self-driving cars and unmanned aerial vehicles. It is also used by police to measure speed, and in gaming, such as the Microsoft Kinect.